Aerodynamic comparison and validation of rans, K-ω, standard K-ɛ and URANS simulations of flat plate film-cooling - Abdulguad, Osama. H. (2014)
Film cooling has been extensively used to provide thermal protection for the external surfaces of gas turbine components. For the past 40 years, numerous number of film cooling hole designs and arrangements have been introduced. Due to broad designs and arrangements of film cooling, numerical investigation has been utilized to provide initial insight on the aerodynamics and thermal performance of the new film cooling designs or arrangements. The present work focuses on the numerical investigation of RANS and URANS analyses on a flat plate film cooling. The investigation aims to provide comparison between various turbulent models available for the Reynolds Average Navier Stokes (RANS) analyses and extended to unsteady Reynolds Average Navier Stokes (URANS). The numerical investigations make used of ANSYS CFX ver. 14 and were carried out at Reynolds Number, Re = 7,000 based on the hole diameter at blowing ratio, BR = 0.5. The results of the RANS analyses show significant influence of the turbulent models on the predicted aerodynamics and thermal performance of the film cooling. Qualitative comparison between the simulation and experimental results shows that standard k-ε produces more accurate results from the other considered turbulent models. In addition to that, results of URANS indicate limitation of RANS analyses to provide details on the eddied and vortices formation in film cooling flow structure.